THE IRONY OF SPAIN’S IMPERIAL DENOUEMENT: AFRANCESAMIENTO IN LEOPOLDO ALAS CLARÍN’S LA REGENTA (1884) (Estudios de Historia de España, 2021)
This article discusses the ironic portrayal of afrancesamiento in Leopoldo Alas Clarín’s La Regenta (1884) as a commentary on geopolitical realities. A well-known Francophile in his time, Clarín frequently employed elements of French culture and language in his literary works. The ironic use of these French elements in La Regenta is viewed as criticism of Spain’s patriarchal system and lack of modernization. I discuss how the afrancesamiento of the Spanish bourgeoisie thematized in La Regenta allows Clarín to comment ironically on attempts to fashion an image of Spain as occidental and superior to orientalized Latin America and its people. This evocation of an imperial context is Clarín’s critique of Spain’s unreadiness to accept the loss of its colonial possessions and to build a modern, post-imperial national identity for itself.
Keywords: Afrancesamiento; loss of colonies; crisis of national identity; traditionalism vs. modernization; critique of patriarchy